THE USE OF COMMUNICATION STRATEGIES BY THE TEACHER AS A TECHNIQUE OF TEACHING TO HELP STUDENTS LEARN TO COMMUNICATE IN ENGLISH ON ELEMENTARY LEVEL IN BALI CHILDREN FOUNDATION - Suarini, Ni Wayan; Seken, I Ketut; Padmadewi, Ni Nyoman (Jurnal Pendidikan Bahasa Inggris undiksha, 2019)
The purposes of this study were to investigate the types of communication strategies used by the teacher as a teachique of teaching to help the students learn to communicate in english, the teacher’s reasons  in applying certain types of communication strategies and the students’ perception toward communication strategies used by the teacher. The data was collected through direct observation, interview, and questionnaire. Besides, mobile recorder, observation sheet and interview guide also used in gaining the data. This study was qualitative research, this type of research was descriptive in which the data taken were automatically analyze descriptively. The result of this study were: there were eigh types of communication strategies applied by the teacher to help students learn to communicate in English, they are literal translation, repetition, language switching, appeal for assistance, topic avoidance, paralanguage, comprehension check and clarification request. (2) There were five main reasons that caused the teacher applied those communication strategies such as to help students to understand the meaning of English utterances, to help students memorized the word in English, to help the students in mastering a topic, to improve students’ motivation in speaking and to help students comprehend the lesson. (3) It can be concluded that communication strategies applied by the teacher in the teaching and learning process can increase the students’ ability in speaking, because the teacher used appropriate communication strategies to help students in learning English.   Key Word:  Communication Strategies, technique of teaching, speaking ability